Гидроэкструзия с дифференцированным противодавлением трубчатой заготовки на подвижной гладкой оправке - Розов, Ю. Г. (НТУ "ХПИ", 2015)
В статье предложена новая перспективная технология гидропрессования ствольной заготовки на подвижной гладкой оправке. Разработанная технология получения длинномерных ствольных заготовок позволяет снизить себестоимость изготовления изделий и повысить продуктивность производства стволов стрелкового оружия, за счёт исключения из технологического процесса методов получения заготовок на специальном оборудовании.

The traditional manufacturing technology of making barreled long-length blanks is made by scheme: preliminary solid deep drilling, reaming, smooth reaming as a finishing operation, honing or drawing, and recently-electrochemical processing. The labour intensiveness of the process increases dramatically. It is proposed the new advanced hydraulic forging technology of the barreled blank on the moving smooth mandrel. The worked out long-length barreled blanks technology enable to cut the manufacturing cost and to increase the production efficiency of small arms barrels, due to the exclusion the methods of receiving the blanks on job-dedicated machinery.
Hydrostatic extrusion with differential back pressure of barreled blank on the moving smooth mandrel
Keywords: гидропрессование; ствол; моделирование; оснастка штамповая; матрица; hydraulic forging; barrel; desing; die tooling; mould